THE MORPHOLOGICAL STATUS OF THE FINALIST IN THROWING DISCIPLINES AT THE BEIJING OLYMPICS - Ratko Pavlović; Zoran Radinović; Marko Janković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Morphological characteristics of the athlete represents his identification card on the base that can be classified as a constitutional type, and also to get information about his body height, body weight, BMI, and even analyze and age. Different constitutional types present in the sport and are important in terms of routing, selection and pursuit of a particular sport. This is expressed especially in athletic sports in the athletics where we have a number of different constitutional types of athletes that requires Discipline. This paper analyzes the morphological status of the finalists in the throwing events at the Olympic Games in Beijing 2008. The survey includes 32 athletes who competed in the finals and the measured variables to assess the morphological status: body height (AVIS), body mass (AMAS), body mass index (BMI), age of the competitor (GOD). Applying basic statistical parameters was performed descriptive analysis of variables applied to the athletes that were made based on the conclusions.